Monitoring, evaluation, learning and impact assessment and scaling preparedness and action (MELIA&SPA): a process-based framework - Minh, Thai Thi (CGIAR Initiative on Rethinking Food Markets, 2022)
Focusing on bundling innovations to co-develop scalable bundles, the Rethinking Food Markets and VCs for Inclusion and Sustainability Initiative develops and applies its monitoring, evaluation, learning and impact assessment, and scaling preparedness and action (MELIA&SPA) framework from a process-based perspective. This MELIA&SPA framework aims to co-developing the scaling preparedness to enhance the scalability of the bundle, and to build market actors’ and relevant stakeholders’ ability to adopt innovation bundles and accelerate the scaling while responding effectively to changes and trade-offs coming. To achieve these, the MELIA (monitoring, evaluation, learning, and impact assessment) emphasizes ensuring the initiative’s impacts on malnutrition reduction, food safety, income and job, small producers’ livelihood, social and gender inclusion, GHG emissions, climate adaptation, and sustainable land and water resources. The SPA (scaling preparedness and actions) enhances the scalability and accelerate the scale of the innovation bundles developed by the Work packages (WPs). The SPA contains exploring intervention and scaling context and options for the piloted innovation bundles, co-designing the piloted innovation bundles with and for the value chain actors, and codeveloping the scaling preparedness and strategies to build the ability for market actors and relevant stakeholders to adopt and accelerate the investment in scalable innovation bundles.